Improving the Performance of Drilling Fluid Using MgO Nano Particles - Falih, Ghufran; Alwasiti, Asawer A.; Alzubaidi, Nada S. (Journal of Petroleum Research and Studies, 2018)
One of the most important factors that cause formation damage is drilling fluid invasion caused by mud filtration. Hence, it is essential to minimize the mud filtration in order to reduce its damage to the formation using drilling fluid additives that control and minimize the filtration rate. Magnesium Oxide (MgO) nanoparticles at different masses (0.01, 0.05, 0.07, 0.1, and 0.2) gm with water base mud have been investigated in this research to measure its effect on the filtration rate. Four types of drilling fluid are used in this research; API water base mud WBM, Saturated salt water mud, DURA THERM mud and polymer mud. Filtration rate was tested under high temperature high pressure (HTHP) conditions; at (75 and 100) C and (500 psi), and at room temperature and pressure at (100 psi). The viscosity of all drilling fluid types is measured using a rotational viscometer at room temperature and atmospheric pressure. In general, the results showed that adding MgO nano particle helped in reducing the filtration rate of drilling fluid, the best results were gained in DURA THERM mud and Saturated Salt Water Mud at MgO concentrationof 0.07gm and 0.2gm, respectively; where the filtrate reduction 60% at 100 C. Also, MgO addition improves rheological properties and drilling fluid stability